Complications When Differentiating Charge Transfer Processes in Electrochemical Capacitor Materials: Assessment of Cyclic Voltammetry Data. Issue 8 (1st January 2019) - Forghani, Marveh; Donne, Scott W.
Abstract : Voltammetric data representing the response of an electrochemical capacitor electrode has been generated containing known contributions from double layer formation, localized and diffusion limited redox processes, electrode instabilities and ohmic resistance. This data has then been modelled using a common approach to differentiating faradaic and non-faradaic processes; namely relating the voltametric current (i(V)) to sweep rate (v); i.e., i(V) = k1 v + k2 v 1/2, where k1 and k2 are constants. Outcomes from the analysis indicate that this approach is complicated by the resistance associated with double layer formation, electrode instabilities in the electrolyte under study, and also increased electrode resistance.